Cognitive Operations in Teachers' Development of Reflective Skills: WANDA Group reflection in a Czech primary school - Jana Poche Kargerová; Petra Vallin; Kamila Etchegoyen Rosolová; Kristýna Bajerová (Charles University, 2020)
In the current rapidly changing world, demands on teacher quality and teacher change are ever- increasing. One important and powerful way to transform schools is through teacher professional development focusing on teachers' reflective skills. But the development of reflective skills is challenging not only from a practical standpoint but also in terms of the demands it places on teachers' cognitive operations. In our study we examined how a specific highly-structured method called WANDA facilitates the development of teachers' reflective skills. WANDA is a form of professional development through group reflection embedded in a five-stage reflective cycle. We connected the stages with cognitive operations employed in the development of reflective skills, and assessed how teachers respond to each stage. Our case study draws on a qualitative research inquiry including semi-structured interviews with nine WANDA participants who teach in a Czech primary school. Our results show that a crucial phase of WANDA that comes early in the process imposes very high demands on teachers' cognitive operations. Teachers might be better prepared to engage in this phase if it comes later in the process and is swapped with another stage that the teachers found highly engaging and fun thanks to its playful form. Overall, WANDA appears to be a meaningful tool in developing teachers' reflective skills, leading them to metacognition, the ultimate peak of self-reflection. Keywords: professional development, WANDA method, group reflection, professional learning communities